2018
DOI: 10.30773/pi.2018.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Electrophysiology by Transcranial Direct Current Stimulation in Psychiatric Disorders: A Systematic Review

Abstract: Objective Transcranial direct current stimulation (tDCS) is a non-invasive neuromodulation technique increasingly used to relieve symptoms of psychiatric disorders. Electrophysiologic markers, such as electroencephalography (EEG) and event-related potentials (ERP), have high temporal resolution sensitive to detect plastic changes of the brain associated with symptomatic improvement following tDCS application. Methods We performed systematic review to identify electrophysiological markers that reflect tDCS effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…EEG mean frequency was also found to be significantly reduced after both anodal and sham tDCS over the left DLPFC, although the effects were smaller for sham tDCS ( Boonstra et al, 2016 ). By contrast, more recent RCTs found no effects on both rest- and task-based EEG power spectrum following anodal tDCS ( Hill et al, 2019 , Holgado et al, 2019 , Miller et al, 2015 ), supporting a quantitative review that indicated little-to-no reliable neural effects of tDCS beyond motor evoked potentials (MEP)( Horvath et al, 2015b ), although these findings might be due to small sample sizes and diverse methodology (e.g., differential measures and protocols) leading to discrepancy across non-clinical studies ( Kim et al, 2018 ).…”
Section: Introductionmentioning
confidence: 65%
“…EEG mean frequency was also found to be significantly reduced after both anodal and sham tDCS over the left DLPFC, although the effects were smaller for sham tDCS ( Boonstra et al, 2016 ). By contrast, more recent RCTs found no effects on both rest- and task-based EEG power spectrum following anodal tDCS ( Hill et al, 2019 , Holgado et al, 2019 , Miller et al, 2015 ), supporting a quantitative review that indicated little-to-no reliable neural effects of tDCS beyond motor evoked potentials (MEP)( Horvath et al, 2015b ), although these findings might be due to small sample sizes and diverse methodology (e.g., differential measures and protocols) leading to discrepancy across non-clinical studies ( Kim et al, 2018 ).…”
Section: Introductionmentioning
confidence: 65%
“…Therefore, neurophysiological markers that can sensitively detect subtle change and serve as an objective indicator of change should be developed. 18,19 However, there has been only one study reported by us; in that study, P50 sensory gating was suggested as a neurophysiological correlate of improvement of auditory hallucination by tDCS. 20 Auditory P300 is a late cognitive event-related potential (ERP) component that reflects attention and working memory update of change.…”
Section: Introductionmentioning
confidence: 91%
“…A similar mechanism of DBS as an explanation for the tDCS effect was also proposed. DBS improves the motor symptoms of PD to restore beta oscillations in the subcortico-cortical functional network, and tDCS could also non-invasively modulate the cortical excitabilities and oscillatory components of the PD brain ( 10 , 23 , 39 , 45 ).…”
Section: Discussionmentioning
confidence: 99%